Reconstruction of Alquran Study with Social Linguistic Approach Method Amin Khulli - Bustami Saladin (LPPM IAIN Sorong, 2020)
Abstract In reconstructing the method of study of the Koran a person must have the ability of Arabic language and literary science as well as an appropriate and qualified methodology to be able to make understanding correctly more in answering social problems. In this context the role of the linguistic approach becomes important in interpreting social verses, both of which are very important in understanding the Qur'an. In understanding the Qur'an to answer social problems, it cannot be separated from one's understanding of the textuality of the verse and the context of social events. that happened at that time. That is why Amin al-Khûlî usesAl Qur'an study methods on social problems with a linguistic approach model Keywords: Amîn al-Khûlî, Linguistic approach, social issues Abstrak Dalam merekonstruksi metode studi al-Qur'ân seseorang harus memiliki kemampuan bahasa Arab dan ilmu kesastraan sekaligus metodologi yang tepat dan mumpuni untuk dapat melakukan pemahaman dengan benar lebih lebi dalam menjawab persoalan sosial kemasyarakatan. Dalam kontreks tersebut peran pendekatan linguistik menjadi penting untuk dalam menginterprestasikan ayat ayat sosial, kedua hal tersebut sangat penting dalam memahami al-Qur'ân Dalam memahami Al-Qur’an untuk menjawab persoalan sosial tidak terlepas dari pemahaman seseorang terahadap tekstualitas ayat dan kotekstualitas kejadian sosial yang terjadi pada waktu itu. Itulah sebabnya Amîn al-Khûlî menggunakan metode studi al Quran terhadap persoalan sosial dengan model pendekatan linguistik Kata Kunci: Amîn al-Khûlî, Pendekatan Bahasa, Isu-isu Sosial